(untitled) (Medico Legal Update, 2021)
Background: India has witnessed a substantial growth in the consumption of plastics and an increased production of plastic waste. Polyolefin account for the major share of 60% in the total plastics consumption in India. Plastic causes major health problems. Aims and Objectives: 1. To assess the knowledge regarding plastic use and its health effects among nursing students. 2. To assess the attitude regarding plastic use and its health effects among nursing students. 3. To determine the relationship between knowledge and attitude regarding plastic use and its health effects among nursing students. 4. To find out the association of knowledge and attitude regarding plastic use and its health effects among nursing students with selected variables. Material and Method: The research approach adopted for the study was quantitative research approach and design was descriptive research design. The study was conducted at selected colleges of Ambala, Haryana. A total of 300 students were selected by using convenience sampling technique. The tool used for the data collection consisted of selected variables, structured knowledge questionnaire and structured attitude scale to measure knowledge of students. Results: Study results revealed that mean score of knowledge was i.e. 59% than mean score of attitude was i.e. 80.3%in the study. A mild positive correlation (r=0.07) was found between knowledge and attitude. There was a significant association of knowledge with gender (p=0.03), academic qualification (p=0.01) and types of school (p= (0.03). There was a significant association of attitude with religion (p=0.00), year (0.00), residence (0.00) and previous knowledge (0.01). Conclusion: Study concluded that the students have average knowledge and moderately favorable attitude regarding plastic use and its health effects.